A coke oven gas desulfurization catalyst and preparation method thereof
By using a modified coal gasification slag titanium dioxide support and reasonable metal active components, the problems of insufficient activity of the coke oven gas desulfurization catalyst and poor conversion effect are solved, and the effects of high activity stability and high conversion of thiophene are achieved. The process is simple and resource utilization is sufficient.
Patent Information
- Application Number
- CN202410424044.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-04-09
AI Technical Summary
The activity of existing coke oven gas hydrodesulfurization catalysts is not long-lasting, the thiophene conversion effect needs to be further improved, and improper treatment of the gasification slag leads to environmental pollution.
The gasification slag was used as the modified titanium dioxide support, and a high activity stability desulfurization catalyst was prepared by adding ethylenediaminetetraacetic acid and ammonium bicarbonate, combining reasonable compound metal active components and adjusting the pH of the impregnation solution.
The activity stability of the catalyst has been improved, the conversion rate of thiophene remains high after 600 hours, and the process is simple and resource utilization is sufficient, making it suitable for industrial production.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a coke oven gas desulfurization catalyst and a preparation method thereof. Background Art
[0002] Coke oven gas is an important product produced in the coking process. It can be used as fuel gas, and can also be used to produce methanol, synthetic liquefied natural gas (LNG), etc. The main components of coke oven gas are hydrogen and methane, and it also contains a small amount of H2S. When coke oven gas is used as fuel, H2S and its combustion product sulfur dioxide are both toxic gases that will seriously damage the atmospheric environment and endanger human health. When used as raw gas, if H2S is not removed, it will corrode the reactor equipment, poison the catalyst, and affect product quality.
[0003] Organic sulfur in coke oven gas includes mercaptans, sulfides, thiophenes, COS and CS2, etc. Compared with substances such as mercaptans and sulfides, thiophene compounds have larger molecular volumes and conjugated π bonds in the molecules, and their molecular structures are more stable, so this type of substance is more difficult to remove. For example, the catalyst for catalytic oxidation of thiophene in diesel, its preparation method and application disclosed in CN202111071994.2, firstly prepared HTC-Al2O3 by in-situ synthesis method, the catalyst has a tailor-made structural design, can control the feasibility of catalytic sites and activity, and then loaded with bimetallic oxides by precipitation method, the catalyst active center is stable, has a large specific surface area, high activity, diesel is desulfurized by oxidation, thiophene is oxidized to sulfoxides, sulfoxides are extremely unstable, and then oxidized to sulfones, sulfones have increased polarity, and are easily removed by adsorption / extraction methods. In diesel, the thiophene conversion rate can reach 96%. Although the catalyst prepared by this method has a good thiophene conversion rate, the preparation method of the catalyst is relatively cumbersome and complicated, which can easily lead to large differences in the activity of catalysts prepared in different batches, and the activity level of the catalyst prepared each time cannot be guaranteed.
[0004] CN201810239284.8 discloses a coke oven gas hydrodesulfurization catalyst and a preparation method thereof, wherein the catalyst uses Al2O3 as a carrier, Mo as an active component, Si as a first promoter, B and / or P as a second promoter, the Mo active component exists in the form of MoO3, the first promoter Si exists in the form of SiO2, the second promoter exists in the form of a second promoter oxide, the second promoter P exists in the form of P2O5, and the second promoter B exists in the form of B2O3. The preparation method of the catalyst first prepares a silicon-molybdenum co-impregnation solution, and then dries and roasts to obtain a catalyst, and the catalyst can be used directly without roasting. The coke oven gas hydrodesulfurization catalyst is a silicon-molybdenum catalyst. Although the initial activity is high and the preparation method is simple, the catalyst activity is not persistent and cannot maintain long-term activity, and the relative thiophene hydrodesulfurization effect needs to be further increased.
[0005] my country's coal resources are relatively abundant. In order to promote the efficient and clean use of resources, the use of coal gasification and coal liquefaction technology has become an effective way. The coal gasification process is a thermochemical process. During the coal gasification process, gasification slag with a high carbon content is produced. At present, the treatment solution for gasification slag is mainly landfill, which will cause serious environmental pollution. Therefore, exploring the rational use of coal gasification slag has become an urgent problem to be solved. Summary of the invention
[0006] Aiming at the problems that the catalyst activity of the coke oven gas hydrodesulfurization catalyst in the prior art is not persistent and cannot maintain activity for a long time, the thiophene conversion effect needs to be further improved, and the current improper treatment method of coal gasification furnace slag is prone to cause environmental pollution, the present invention provides a coke oven gas desulfurization catalyst.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] A coke oven gas desulfurization catalyst, the preparation method of which is as follows:
[0009] S1: adding coal gasification furnace slag to the prepared titanium salt solution, stirring, adding ethylenediaminetetraacetic acid, maintaining the stirring temperature and speed and continuing to stir, after the stirring is completed, filtering the precipitate, putting it into an oven for drying, and roasting to obtain the titanium dioxide carrier modified by coal gasification furnace slag;
[0010] S2: dissolving soluble salts containing cesium, nickel, calcium and copper in deionized water, adding acid to adjust the pH, and stirring to prepare an impregnation solution;
[0011] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution, and after standing for a period of time, the catalyst is prepared after filtering, drying and roasting.
[0012] Furthermore, the coal gasification furnace slag is mechanically ground in advance to obtain fine powder, and the fine powder is sieved through a 300-mesh sieve and then used to prepare the carrier.
[0013] Furthermore, the mass ratio of the coal gasification slag to the titanium salt is 50-85:100.
[0014] Furthermore, the method for preparing the titanium salt solution is as follows: in the process of dissolving the titanium salt in deionized water, ethanol and ammonium bicarbonate are added, and the mixture is stirred and dissolved for later use;
[0015] The volume ratio of the ethanol, ammonium bicarbonate and deionized water is 0.1-1:0.2-0.5:1, and the titanium salt is titanyl sulfate.
[0016] Furthermore, the stirring temperature is 30-50° C., and the stirring speed is 100-200 rpm.
[0017] Furthermore, the soluble salt containing cesium, nickel, calcium and copper is one of nitrate and sulfate, and the molar ratio of the metal components cesium, nickel, calcium and copper in the soluble salt containing cesium, nickel, calcium and copper is 0.5-3:5-13:2-6:1-7:
[0018] Preferably, the molar ratio of the metal components cesium, nickel, calcium and copper in the soluble salt containing cesium, nickel, calcium and copper is 0.5:8:2:3.
[0019] Furthermore, the acid is one of citric acid and acetic acid, and the pH is adjusted to 3.5-5;
[0020] Preferably, the acid is acetic acid, and the pH is adjusted to 4.
[0021] Furthermore, the titanium dioxide carrier modified by coal gasification furnace slag is impregnated in the impregnation solution for 6 to 8 hours, and the impregnation is performed in equal volume.
[0022] Furthermore, the filtered sample was placed in a drying oven at 80°C for 24 hours, and the dried sample was placed in a muffle furnace. The heating rate of the muffle furnace was set to 3°C / min, and this heating rate was maintained from room temperature to 750°C. The sample was calcined at 750°C for 8 hours, and the calcined sample was ground into powder and a standard sieve was used to sieve out an 80-mesh catalyst sample.
[0023] A catalyst obtained by any of the above-mentioned methods for preparing the catalyst.
[0024] The present invention has the following beneficial effects:
[0025] 1. The coke oven gas desulfurization catalyst provided by the present invention uses coal gasification furnace slag as a modifier in the preparation process of the titanium dioxide carrier, and by adding ethylenediaminetetraacetic acid and a pore-enlarging agent ammonium bicarbonate, the finally prepared desulfurization catalyst has a higher activity stability energy and can still have a high thiophene conversion rate after 600 hours of reaction, thereby effectively improving the activity stability of the desulfurization catalyst.
[0026] 2. The coke oven gas desulfurization catalyst provided by the present invention can obtain a good thiophene conversion rate by reasonably compounding metal active components during the preparation process.
[0027] 3. The coke oven gas desulfurization catalyst provided by the present invention can well control the thiophene conversion rate of the desulfurization catalyst by adjusting the final pH value during the preparation of the impregnation solution.
[0028] 4. The preparation method of the catalyst provided by the present invention has a simple preparation process and makes good use of coal gasification slag, thereby achieving full utilization of resources. Moreover, the entire preparation process of the catalyst is easy to control, which is convenient for expanding production. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments.
[0030] The chemical reagents described in the following embodiments of the present invention can all be purchased directly from the market.
[0031] Example 1
[0032] S1: The coal gasification furnace slag is mechanically ground in a grinder (dry grinding machine of NETZSCH, Germany) to obtain fine powder, and the fine powder is sieved through a 300-mesh sieve for later use.
[0033] Preparation of titanium salt solution: prepare ethanol, ammonium bicarbonate and deionized water in a volume ratio of 0.5:0.3:1 to prepare a standby solvent, then add titanyl sulfate dihydrate into the standby solvent in a mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate of 60:100, stir until completely dissolved and set aside.
[0034] Similarly, the sieved coal gasification slag is placed in the prepared titanium salt solution according to the mass ratio of coal gasification slag to titanium sulfate dihydrate of 60:100, and ethylenediaminetetraacetic acid is added while stirring. The mass of the added ethylenediaminetetraacetic acid is 1 / 10 of the mass of the coal gasification slag. The stirring process is maintained at a temperature of 30°C and a stirring speed of 200rpm. After the stirring is completed, the precipitate is filtered and placed in an oven at 100°C until it is dried, and then placed in a muffle furnace and roasted at 800°C for 8h to obtain a titanium dioxide carrier modified by coal gasification slag;
[0035] S2: dissolving nitrates containing cesium, nickel, calcium and copper in deionized water according to the corresponding metal molar ratio of 0.5:8:2:3, adding acetic acid to adjust the pH to 4 after complete dissolution, and preparing an impregnation solution after stirring evenly;
[0036] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution and impregnated with equal volume for 8 hours. The filtered sample is placed in a drying oven and kept warm at 80°C for 24 hours. The dried sample is placed in a muffle furnace and the heating rate of the muffle furnace is set to 3°C / min. The heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, and the calcined sample is ground into powder and a 80-mesh catalyst sample is sieved out using a standard sieve.
[0037] Example 2
[0038] S1: Grind the coal gasification furnace slag in a grinder to obtain fine powder, and sieve the fine powder through a 200-mesh sieve for later use.
[0039] Preparation of titanium salt solution: prepare ethanol, ammonium bicarbonate and deionized water in a volume ratio of 0.1:0.2:1 to prepare a standby solvent, then add titanyl sulfate dihydrate into the standby solvent in a mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate of 80:100, stir until completely dissolved and set aside.
[0040] Similarly, the sieved coal gasification slag is placed in the prepared titanium salt solution according to the mass ratio of coal gasification slag to titanium sulfate dihydrate of 80:100, and ethylenediaminetetraacetic acid is added while stirring. The mass of the added ethylenediaminetetraacetic acid is 1 / 10 of the mass of the coal gasification slag. The stirring process is maintained at a temperature of 50°C and a stirring speed of 200 rpm. After the stirring is completed, the precipitate is filtered and placed in an oven at 100°C until it is dried, and then placed in a muffle furnace and roasted at 800°C for 8 hours to obtain a titanium dioxide carrier modified by coal gasification slag;
[0041] S2: dissolving nitrates containing cesium, nickel, calcium and copper in deionized water according to the corresponding metal molar ratio of 0.5:5:2:7, adding acetic acid to adjust the pH to 5 after complete dissolution, and stirring to prepare an impregnation solution;
[0042] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution and impregnated with equal volume for 8 hours. The filtered sample is placed in a drying oven and kept warm at 80°C for 24 hours. The dried sample is placed in a muffle furnace and the heating rate of the muffle furnace is set to 3°C / min. The heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, and the calcined sample is ground into powder and a 80-mesh catalyst sample is sieved out using a standard sieve.
[0043] Example 3
[0044] S1: Grind the coal gasification furnace slag in a grinder to obtain fine powder, and sieve the fine powder through a 300-mesh sieve for later use.
[0045] Preparation of titanium salt solution: prepare ethanol, ammonium bicarbonate and deionized water in a volume ratio of 0.5:0.5:1 to prepare a standby solvent, then add titanyl sulfate dihydrate into the standby solvent in a mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate of 50:100, stir until completely dissolved and set aside.
[0046] Similarly, the sieved coal gasification slag is placed in the prepared titanium salt solution according to the mass ratio of coal gasification slag to titanium sulfate dihydrate of 50:100, and ethylenediaminetetraacetic acid is added while stirring. The mass of the added ethylenediaminetetraacetic acid is 1 / 10 of the mass of the coal gasification slag. The stirring process is maintained at a temperature of 30°C and a stirring speed of 200 rpm. After the stirring is completed, the precipitate is filtered and placed in an oven at 100°C until it is dried, and then placed in a muffle furnace and roasted at 800°C for 8 hours to obtain a titanium dioxide carrier modified by coal gasification slag;
[0047] S2: dissolving nitrates containing cesium, nickel, calcium and copper in deionized water according to the corresponding metal molar ratio of 3:8:6:1, adding acetic acid to adjust the pH to 4 after complete dissolution, and preparing an impregnation solution after stirring evenly;
[0048] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution and impregnated with equal volume for 8 hours. The filtered sample is placed in a drying oven and kept warm at 80°C for 24 hours. The dried sample is placed in a muffle furnace and the heating rate of the muffle furnace is set to 3°C / min. The heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, and the calcined sample is ground into powder and a 80-mesh catalyst sample is sieved out using a standard sieve.
[0049] Example 4
[0050] S1: Grind the coal gasification furnace slag in a grinder to obtain fine powder, and sieve the fine powder through a 300-mesh sieve for later use.
[0051] Preparation of titanium salt solution: ethanol, ammonium bicarbonate and deionized water are prepared into a standby solvent in a volume ratio of 0.2:0.3:1, and then titanyl sulfate dihydrate is added into the standby solvent in a mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate of 85:100, and stirred until completely dissolved for use.
[0052] Similarly, the sieved coal gasification slag is placed in the prepared titanium salt solution according to the mass ratio of coal gasification slag to titanium sulfate dihydrate of 85:100, and ethylenediaminetetraacetic acid is added while stirring. The mass of the added ethylenediaminetetraacetic acid is 1 / 10 of the mass of the coal gasification slag. The stirring process is maintained at a temperature of 30°C and a stirring speed of 200 rpm. After the stirring is completed, the precipitate is filtered and placed in an oven at 100°C until it is dried, and then placed in a muffle furnace and roasted at 800°C for 8 hours to obtain a titanium dioxide carrier modified by coal gasification slag;
[0053] S2: dissolving nitrates containing cesium, nickel, calcium and copper in deionized water according to the corresponding metal molar ratio of 3:13:2:1, adding acetic acid to adjust the pH to 3 after complete dissolution, and preparing an impregnation solution after stirring evenly;
[0054] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution and impregnated with equal volume for 8 hours. The filtered sample is placed in a drying oven and kept warm at 80°C for 24 hours. The dried sample is placed in a muffle furnace and the heating rate of the muffle furnace is set to 3°C / min. The heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, and the calcined sample is ground into powder and a 80-mesh catalyst sample is sieved out using a standard sieve.
[0055] Example 5
[0056] S1: Grind the coal gasification furnace slag in a grinder to obtain fine powder, and sieve the fine powder through a 300-mesh sieve for later use.
[0057] Preparation of titanium salt solution: ethanol, ammonium bicarbonate and deionized water are prepared into a standby solvent in a volume ratio of 0.3:0.5:1, and then titanyl sulfate dihydrate is added into the standby solvent in a mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate of 60:100, and stirred until completely dissolved for use.
[0058] Similarly, the sieved coal gasification slag is placed in the prepared titanium salt solution according to the mass ratio of coal gasification slag to titanium sulfate dihydrate of 60:100, and ethylenediaminetetraacetic acid is added while stirring. The mass of the added ethylenediaminetetraacetic acid is 1 / 10 of the mass of the coal gasification slag. The stirring process is maintained at a temperature of 30°C and a stirring speed of 200rpm. After the stirring is completed, the precipitate is filtered and placed in an oven at 100°C until it is dried, and then placed in a muffle furnace and roasted at 800°C for 8h to obtain a titanium dioxide carrier modified by coal gasification slag;
[0059] S2: dissolving nitrates containing cesium, nickel, calcium and copper in deionized water according to the corresponding metal molar ratio of 3:13:2:7, adding citric acid to adjust the pH to 4 after complete dissolution, and preparing an impregnation solution after stirring evenly;
[0060] S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution and impregnated with equal volume for 8 hours. The filtered sample is placed in a drying oven and kept warm at 80°C for 24 hours. The dried sample is placed in a muffle furnace and the heating rate of the muffle furnace is set to 3°C / min. The heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, and the calcined sample is ground into powder and a 80-mesh catalyst sample is sieved out using a standard sieve.
[0061] Example 6
[0062] During the preparation of the carrier, the titanium dioxide carrier was not modified by the gasified slag, and the other aspects were the same as the catalyst preparation method in Example 1.
[0063] Example 7
[0064] During the preparation of the carrier, the mass ratio of coal gasification furnace slag to titanyl sulfate dihydrate was 30:100, and the other parts were the same as the catalyst preparation method in Example 1.
[0065] Example 8
[0066] During the preparation of the carrier, ethylenediaminetetraacetic acid was replaced with citric acid, and the other ingredients were the same as the catalyst preparation method in Example 1.
[0067] Example 9
[0068] During the catalyst preparation process, the nitrates of cesium, nickel, calcium and copper are prepared in a corresponding metal molar ratio of 0.1:15:1:10, and the other aspects are the same as the catalyst preparation method of Example 1.
[0069] Example 10
[0070] During the catalyst preparation process, the nitrates of nickel, calcium and copper are prepared in a molar ratio of 8:2:3 to their corresponding metals. Other aspects are the same as the catalyst preparation method of Example 1.
[0071] Embodiment 11
[0072] During the catalyst preparation process, the pH was adjusted to 6.5 in step S2, and the rest was the same as the catalyst preparation method in Example 1.
[0073] Example 12
[0074] During the catalyst preparation process, in step S2, acetic acid is replaced with ethylenediaminetetraacetic acid to adjust the pH to 4, and the rest is the same as the catalyst preparation method in Example 1.
[0075] Catalyst activity testing
[0076] Catalyst evaluation was carried out on a fixed bed reactor. 10 g of the prepared catalyst was taken and placed in the bed of a quartz tube fixed bed reactor. N2 was first passed through to ensure that there was no leakage before conducting the experiment. The catalyst was pre-sulfurized with CS2 at 400°C for 2 hours, and then the N2 was switched to purge the bed while cooling. After the temperature dropped to 200°C, the raw gas was switched. In order to make the raw gas close to the industrial coke oven gas containing a certain amount of water vapor, the raw gas first passed through deionized water before entering the reactor. After the reaction was stable for 1.5 hours, a sample was taken with a syringe, diluted with nitrogen, and injected into a trace sulfur analyzer for analysis. Catalytic reaction conditions: normal pressure, reaction temperature 340°C, space velocity 1500h-1, thiophene inlet concentration 450mg / m 3 The simulated coke oven gas was purchased from Beijing Hepu North Gas Industry Co., Ltd. The thiophene conversion rate R (%) was calculated according to formula (1).
[0077] R=(M0-M1) / M0 Formula (1)
[0078] In formula (1), M0 and M1 are the concentrations of thiophene in the gas at the reactor inlet and outlet, respectively, in mg / m 3 .
[0079] The gas after the reaction was detected by a trace sulfur analyzer, which was an SP-6600A trace sulfur analyzer produced by Beijing Putin Chromatography Technology Co., Ltd., with a GDX chromatographic column and an FPD flame photometric detector, and the detection limit of sulfur was 0.05 ppm. The ZB-2010 chromatographic workstation software was used for analysis, and the standard gas containing thiophene was used for calibration before use.
[0080] According to the above-mentioned catalyst activity detection method, the catalysts prepared in Example 1 and Examples 6-8 were subjected to activity detection, and the initial thiophene conversion rate of the reaction and the thiophene conversion rate after 600 hours of reaction were detected respectively, so as to judge the activity stability of the catalyst. The specific detection results are shown in Table 1.
[0081] Table 1
[0082] Catalyst samples Initial thiophene conversion rate (%) Thiophene conversion rate after 600h reaction (%) Example 1 99.8% 89.9% Example 2 98.7% 88.9% Example 3 99.2% 86.9% Example 4 98.4% 87.3% Example 5 99.5% 84.1% Example 6 80.9% 61.5% Example 7 83.1% 72.9% Example 8 98.6% 74.1%
[0083] From the test results of the above data, it can be seen that the preparation process of the carrier did not undergo modification of the gasification slag or change the mass ratio of the gasification slag to the titanium salt precursor compound. The catalyst finally prepared showed an obvious downward trend in conversion rate both in terms of initial thiophene conversion rate and activity stability.
[0084] According to the experimental results of Example 8, when ethylenediaminetetraacetic acid was replaced with citric acid during the carrier preparation process, the initial thiophene conversion rate of the catalyst finally prepared showed the result of coking, but after the reaction lasted for 600 hours, the problem of decreased activity stability occurred.
[0085] In order to further detect the effect of various conditions in the catalyst preparation process on the thiophene conversion activity of the final catalyst, the initial thiophene conversion rates of Example 1 and Examples 9-12 were specifically detected. The specific results are summarized in Table 2 below.
[0086] Table 2
[0087] Catalyst samples Initial thiophene conversion rate (%) Example 1 99.8% Example 9 90.3% Example 10 85.6% Embodiment 11 88.1% Example 12 93.7%
[0088] During the catalyst preparation process, if the active components in the catalyst are changed or the active components do not contain metallic cesium, the final initial thiophene conversion rate will be significantly reduced.
[0089] In addition, during the preparation of the impregnation solution, the initial thiophene conversion rate was also significantly reduced by changing the final pH of the impregnation solution. However, when the acid for adjusting the pH was changed to ethylenediaminetetraacetic acid, the thiophene conversion rate decreased. However, compared with the changes in other conditions, the decrease in the initial thiophene conversion rate of the corresponding catalyst was not particularly obvious.
Claims
1. A coke oven gas desulfurization catalyst, characterized in that: The preparation method is as follows: S1: adding coal gasification furnace slag to the prepared titanium salt solution, stirring, adding ethylenediaminetetraacetic acid, maintaining the stirring temperature and speed and continuing to stir, after the stirring is completed, filtering the precipitate, putting it into an oven for drying, and roasting to obtain the titanium dioxide carrier modified by coal gasification furnace slag; S2: dissolving soluble salts containing cesium, nickel, calcium and copper in deionized water, adding acid to adjust the pH, and stirring to prepare an impregnation solution; S3: The titanium dioxide carrier modified by coal gasification furnace slag is placed in the impregnation solution, and after standing for a period of time, the catalyst is prepared after filtering, drying and roasting.
2. The catalyst according to claim 1, characterized in that The coal gasification furnace slag is pre-ground mechanically to obtain fine powder, and the fine powder is sieved through 200-300 meshes to be used for preparing the carrier.
3. The catalyst according to claim 1, characterized in that The mass ratio of the coal gasification furnace slag to the titanium salt is 50-85:
100.
4. The catalyst according to claim 1, characterized in that The method for preparing the titanium salt solution is as follows: when dissolving the titanium salt in deionized water, ethanol and ammonium bicarbonate are added, and the mixture is stirred and dissolved for later use; The volume ratio of the ethanol, ammonium bicarbonate and deionized water is 0.1-1:0.2-0.5:1, and the titanium salt is titanyl sulfate.
5. The catalyst according to claim 1, characterized in that In step S1, the stirring temperature is 30-50° C., and the stirring speed is 100-200 rpm.
6. The catalyst according to claim 1, characterized in that In step S2, the soluble salt containing cesium, nickel, calcium and copper is one of nitrate and sulfate, and the molar ratio of the metal components cesium, nickel, calcium and copper in the soluble salt containing cesium, nickel, calcium and copper is 0.5-3:5-13:2-6:1-7.
7. The catalyst according to claim 6, characterized in that The molar ratio of the metal components cesium, nickel, calcium and copper in the soluble salt containing cesium, nickel, calcium and copper is 0.5:8:2:
3.
8. The catalyst according to claim 1, characterized in that In step S2, the acid is one of citric acid and acetic acid, and the pH is adjusted to 3.5-5.
9. The catalyst according to claim 8, characterized in that The acid is acetic acid, and the pH is adjusted to 4.
10. The catalyst according to claim 1, characterized in that In step S3, the titanium dioxide carrier modified by coal gasification furnace slag is impregnated in the impregnation solution for 6 to 8 hours, and the impregnation is performed in equal volume.
11. The catalyst according to claim 1, characterized in that In step S3, the filtered sample is placed in a drying oven at 80°C for 24 hours, the dried sample is placed in a muffle furnace, the heating rate of the muffle furnace is set to 3°C / min, and this heating rate is maintained from room temperature to 750°C. The sample is calcined at 750°C for 8 hours, the calcined sample is ground into powder, and a standard sieve is used to sieve out an 80-mesh catalyst sample.
Citation Information
Patent Citations
A catalyst for hydrodesulfurization of coke oven gas and its preparation method
CN108404901B
Catalysts for the catalytic oxidation of thiophene in diesel oil, their preparation methods and applications
CN113856736B
Desulfurization catalyst for hydrocarbon oil and preparation method for desulfurization catalyst for hydrocarbon oil and desulfurization method for hydrocarbon oil
CN105312074A
Preparation method of novel SCR smoke denitrification catalyst adopting titanium-containing blast furnace slag as carrier
CN105327698A